Assessing Sediment Transport and Shoreline Dynamics in High-Energy Tropical Coasts - Umar, Hasdinar; Paotonan, Chairul; Rachman, Taufiqur; Nur, Sitti Hijraini; Muhiddin, Amir H.; Maming, Muhammad Idhil; Andriadi, Andi M. Rezky; Assidiq, Fuad Mahfud (Salehan Institute of Higher Education, 2025)
This research examines coastal erosion in North Galesong, Indonesia, by validating longshore sediment transport (LST) equations and predicting shoreline changes over ten years. To evaluate sediment movement and coastline alterations, it integrates field data on sediment grain size and wave characteristics with numerical modeling techniques, including the CERC equation and finite difference methods. Sieve analysis revealed a range of sediment textures (D50: 0.17–0.65 mm), predominantly medium-fine sand. Wave analysis indicated a dominance of moderate energy southwesterly waves (1.5 m height, 6.39 s period) that aid sediment transport. The empirical LST models, calibrated with local data, closely matched numerical simulations (error <20%), predicting an annual net northward sediment transport of 406,869 m³. Shoreline analysis across 15 segments showed significant spatial variability: severe erosion occurred in Cell 4 (Δy = -0.82 m), while Cell 3 saw accretion (Δy = +0.68 m), influenced by wave direction, sediment supply, and coastal morphology. This study underscores the value of hybrid empirical-numerical methods in data-scarce regions and emphasizes the need for local model calibration to enhance coastal resilience. The findings inform sustainable management practices, promoting adaptive strategies to address sediment imbalances and hydrodynamic changes due to climate factors.